A retrospective examination of antisocial and risk-taking behaviours. Issue 4 (4th July 2019) - Brindle, Kimberley A.; Bowles, Terence V.; Freeman, Elizabeth
Abstract : Engagement in antisocial and risk-taking behaviours is a recurring issue that has been associated with a range of negative outcomes for the individual, community, and society. This research explored factors that influenced engagement and co-occurring behaviours. Responses ( n  = 393) from an Australian sample who completed the Antisocial Engagement Questionnaire showed that the majority of the behaviours of interest were associated, indicating that engagement in one behaviour was associated with engagement in additional antisocial and risk-taking behaviours. Engagement in antisocial behaviours was also associated with increased substance consumption. An investigation into the associations between 15 substance-related behaviours found that use of one substance was associated with the use of additional substances. The findings have implications for understanding the development of an antisocial lifestyle, the associations between behaviours, the findings build on research relating to behaviour prediction and will assist clinicians working with at-risk individuals and intervention design.